2008
DOI: 10.1159/000165117
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Fatal Cases of Chinese Patients with Primary Antineutrophil Cytoplasmic Antibodies-Associated Renal Vasculitis: A 10-Year Retrospective Study

Abstract: Background/Aims: Primary antineutrophil cytoplasmic antibodies (ANCA)-associated systemic vasculitis (AASV) used to have poor prognosis, and renal involvement is its most common manifestation. Few studies have been published focusing on AASV patients with poor prognosis. Methods: From 1997 to 2006, 101 patients with ANCA-associated renal vasculitis (70 microscopic polyangiitis, MPA; 14 Wegener’s granulomatosis, WG; 3 Churg-Strauss syndrome, CSS; 14 renal limited vasculitis, RLV) were diagnosed in Shanghai Ruij… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
2
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 43 publications
(26 reference statements)
0
26
2
4
Order By: Relevance
“…We found that infection, in combination with the pulmonary involvement of active vasculitis was an important cause of death, this is consistent with earlier studies. [1623] Previous studies on severe infection and therapy-related death in AAV patients have reported that pulmonary involvement (especially pulmonary hemorrhage) was an independent predictor of mortality. [1521] Vasculitis activity may, therefore, be partly responsible for the infection-related deaths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that infection, in combination with the pulmonary involvement of active vasculitis was an important cause of death, this is consistent with earlier studies. [1623] Previous studies on severe infection and therapy-related death in AAV patients have reported that pulmonary involvement (especially pulmonary hemorrhage) was an independent predictor of mortality. [1521] Vasculitis activity may, therefore, be partly responsible for the infection-related deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies on the outcome of subgroup with renal involvement showed that in addition to the decreased renal function, many other factors were associated with early death, including advanced age, high Birmingham Vasculitis Activity Score (BVAS), therapy-related adverse events, pulmonary hemorrhage, renal insufficiency, etc . [121314151617] However, patient selection criteria and the choice of predictors of mortality have not been uniform in the studies conducted to date. A few studies have been conducted on the predictors of mortality in AAV patients in China.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Yong-Xi Chen et al, with 101 patients, the mortality rate at 1 year was 18.8%, and 32.9% at 5 years. 23 In the study by Day et al, with 390 patients including cases of AAV and renal involvement, 18% of patients at 5 years required renal replacement treatment and 40% died. 21 In our study, the mean follow-up was 4.1 years (1.5-12 years) with a median of 3 years, during which 60% of patients underwent renal replacement therapy, and 12% died.…”
Section: Discussionmentioning
confidence: 99%
“…ELISA was performed to test antimyeloperoxidase (MPO) and antiproteinase 3 (PR3) antibodies in all sera (Euroimmun AG) as reported 4,9 . All patients had been tested for the presence of ANCA by IIF (Euroimmun AG, Lubeck, Germany).…”
Section: Rheumatologymentioning
confidence: 99%